Legal and economic interfaces between antidumping and competition policy - Tavares de Araujo, José (ECLAC SantiagoCL, 2001)
Summarizes the current debate about antidumping rules in the United States. Reviews the instruments used by the European Union and the US government for reconciling a strong enforcement of competition laws with an intense use of antidumping measures. Highlights some pecularities of the FTAA process.